DNA-markers of heterosis of sunflower hybrids of domestic breeding - A. V. Usatov; M. S. Makarenko; O. F. Gorbachenko; K. V. Azarin; A. A. Kovalevich; P. I. Kostylev; N. V. Markin (Зерновое хозяйство России, 2018)
DNA-markers of heterosis of sunflower hybrids of domestic breeding The article presents the results of the analysis of polymorphism conducted on micro satellite loci of core genome by 12 SSR-markers (Ha 432, Ha 514, Ha 1442, Ha 1608, Ha1287, IUB6, ORS6, ORS 509, IUB4, HNCA1, OSU-1, HNCA2). Seven genotypes of the hybrid F1 of sunflower (Donskoy 151 -♀ВД 151 х ♂ ВД 541; Partner - ♀ ЭД 1443 х ♂ВД 541; Donskoy 22 - ♀ВД 22 х ♂ВД 541; Garant - ♀ЭД 931 х ♂ВД 62; Prestizh - ♀ЭД 169 х ♂ВД 62; Signal - ♀ЭД 236 х ♂ВД 110; Donskoy 1448 - ♀ВД 1448 х ♂ВД 62) and their parental lines developed by the Donskaya Experimental Station named after L.A. Zhdanov have been analyzed. 36 allelic variants have been established. For each genotype there has been designed a separate allelic formula which can be used as its molecule-genetic passport. The studied marker system has a high discrimination potential for identifying sunflower selection samples. The heterosis of hybrid F1, genetic diversity of parental lines based on SSR-markers as well as genetic distances with combination ability of sunflower have been studied. Ten basic inbred lines (3 Rf lines and 7 CMS lines) and their hybrids have been studied according to such traits as height, plant productivity, 1000-kernels weight, oil content and hull content. The field trials were conducted during 6 seasons. Genetic distance among parental lines of sunflower ranged from 0.45 to 0.74. There has been found a reliable positive correlation of heterosis effect on the yield of seeds in hybrids (r=0.79, р